STUDI PENGARUH LAJU ALIR LARUTAN PADA SISTEM DESALINASI METODE FLOW-THROUGH CAPACITOR (FTC) DENGAN ELEKTRODA DARI KARBON AKTIF DAN CARBON NANOTUBES (CNT) - Romi Buana Puja Pangestu; Agus Subagio (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
The electrodes are made of a combination between the CNT and the activated carbon had been created as a method of desalination systems the flow-through capacitor (FTC). The FTC is one method desalination done by flowing salt water passed the between electrodes based on the principle capacitor. The addition of the CNT on activated carbon as electrode will hopefully increase the conductivity and resistivity on activated carbon reduces that provides increased absorption. System optimization testing FTC desalination is carried out by the time of voltage and variation flow rate solution.Fabrication of electrodes are made of mixed a primary ingredient CNT to the activated carbon with a comparison of 10:90 (% wt) and urotropin to the phenolic resin Binder ratio10:90 (% wt). Comparison of carbon : fastener end of 80:20. The electrodes are formed with method of hot-pressing and heated for 30 minutes at a temperature of 1800C . The electrodes are resistance tested and characterized using SEM to saw the shape of the morphology of the electrodes.Prototype tested results with 7 pairs of electrodes 10% CNT could separated a compound salt of solution 1785 mg/L during 120 minutes with a flow rate 5 mL/min of 57%. Tested by conduktivitimeter at flow rate variation 5, 15, 25, and 35 mL/min had the lowest concentration of the solution on the reduction in flow rate 5 mL/min. But the solution that had passed through the electrodes on the low flow are much less than with a high flow rate.Keywords : Electrodes, desalination, FTC, CNT, activated carbon.